Grammatical Cohesion and Textuality: An Argumentative Discussion - Surdyanto, Annas (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
The article discusses the grammatical cohesion and textuality by relating preceding linguistic discussions with some use cases found in real life. The discussion involves Reference: anaphoric, cataphoric, and exophoric. Besides, this article also discusses ellipsis and substitution. As an addition. Conjunction is also discussed in this article. Grammatical cohesion impacts the texture of text. The textuality comes from the concept of grammatical cohesion that speaker and writer apply to express language. The discussion confirms that the correlation between grammatical cohesion and textuality. The reference, ellipsis and substitution and conjunction in grammatical cohesion indicates the texture of utterances in language.